Evolutionary stakeholder theory and public utility regulation. (22nd May 2019) - Kline, William; McDermott, Karl
Abstract: Public utility regulation is one example of how stakeholder theory has actually evolved in practice. Through trial and error, court cases, statutory law and economic realities, stakeholder theory has its origins almost a century before R Edward Freeman published his seminal work Strategic Management: A Stakeholder Approach . This wealth of historical data is largely overlooked by the stakeholder literature. We will show in this article how the specific history of public utility regulation provides at least one answer to how stakeholder theory can be formulated, used, and applied. This process of determining and protecting stakeholder interests is significantly different from rationalist trends in stakeholder theory. 1 Rather than first trying to determine the requirements of stakeholder theory in conjunction with an ideal ethical theory, the account given here is of an evolutionary stakeholder theory where rules arise out of the ongoing search for cooperative solutions among all stakeholders.